Upaya Peningkatan Kualitas Pelayanan Publik di Kelurahan Wonorejo Kecamatan Gondangrejo Kabupaten Karanganyar - Joko Kismanto; Agustina Pujilestari; Sely Aprianda Syah Putri; Sufina Pintu; Muhammad Husin Nur Muzakki (Universitas Muhammadiyah Semarang, 2026)
At the village level, the quality of public services is often the most immediate indicator for the community to assess whether the government serves citizens’ needs or merely functions as an administrative institution. When services are delivered slowly, unclearly, and without responsiveness, people will immediately perceive weaknesses in government governance. On the other hand, when village officials provide well-organized, easy-to-understand, and responsive services, public services can function not only as a means of resolving administrative matters but also as a medium for strengthening public trust in the village government. Based on this perspective, this community service activity was conducted to enhance the understanding of Wonorejo Village officials regarding Minimum Service Standards for Villages and their relevance to daily public service practices. The activity began with field observations and was followed by face-to-face counseling sessions for village government officials. The results demonstrated an improvement in participants’ understanding after the counseling activities were conducted. These findings indicate that strengthening village officials’ knowledge regarding village service standards can serve as an important foundation for improving the quality of public services within village governance.